The impact of critical feedback choice on students' revision, performance, learning, and memory. (January 2018) - Cutumisu, Maria; Schwartz, Daniel L.
Abstract: This article examines empirically the impact of students' critical feedback choices on their memory for feedback. It also examines the effect of choosing versus receiving feedback on learning outcomes. First, a correlational study was designed to collect the choices to seek critical feedback and to revise posters from a hundred and six Grade 8 middle-school students via Posterlet, a digital assessment game in which students design posters. Upon completing the game, students filled a post-test asking them to freely recall the feedback messages they encountered in Posterlet. Results show that, when they have a choice between critical and confirmatory feedback, students tend to remember critical feedback better than confirmatory feedback. Second, a yoked experiment was designed to compare the performance and learning of college students who chose and were assigned the same amount and order of critical feedback, respectively. Results show that 1) critical feedback and revision are positively associated with performance when students choose their feedback, while critical feedback is negatively associated with learning when students receive their feedback; 2) students who engaged with higher levels of critical feedback significantly outperformed the rest of the participants only if they had a choice over their feedback; and 3) students enjoy designing posters significantly more when they choose rather than receive their feedback. Ramifications for student learning are discussed. Future work will examine whether there are any differences in memory for feedback between students who choose and those who are assigned the same amount and order of critical feedback. Highlights: The impact of middle-school students' feedback agency on their memory for feedback was examined. The effect of choosing versus receiving critical feedback on college students' performance and learning was also investigated. Results show that critical feedback is better remembered than confirmatory feedback. Students who engaged with higher levels of critical feedback significantly outperformed the rest of the participants only if they had a choice over their feedback. Students enjoy designing posters significantly more when they choose rather than receive their feedback.